Supporting Young Digital Workers: Acknowledging the Real Vulnerabilities of Gig Work in Today’s Marketplace System - Hilda Rahmah; Fitra Prasapawidya Purna; Sri Syamsiyah Lestari Sjafiie; Yoma Bagus Pamungkas (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to explore the vulnerabilities faced by young digital workers in the marketplace and see how these young workers cope with the increasingly complex challenges of partnership-based work. The growth of the freelance economy has presented new challenges for young workers in Indonesia. These vulnerabilities arise from the partnership-based work system, which frees companies from the obligation to pay workers the regional minimum wage, ensure occupational safety and health, or provide overtime compensation. The freelance economy has resulted in job creation through platforms that   work flexibility, making freelance work attractive to young individuals seeking flexible work. This study uses an ethnography method to explore the community of young digital workers using a partnership system in the marketplace. Data in the study were obtained through virtual interviews and observations of young people’s work activities in the marketplace. The research findings reveal that the flexibility offered by the platform work system presents a paradox of vulnerability. On the one hand, workers value the freedom to work without time constraints. However, on the other hand, they simultaneously struggle with uncertain working conditions, including low wages, social discrimination, and lack of job security. This vulnerability makes them aware and encourages them to seek social support by joining telegram or WhatsApp courier groups, freelance live streamer communities, creative worker forums and doing double jobs without the platform’s knowledge. Furthermore, they create daily tactics by exploiting loopholes in the bonus or incentive system, such as accepting fictitious orders and splitting accounts. Vulnerability makes them a more preventive risk society. Furthermore, this action is a daily political practice that represents silent resistance as an effort to resist platform dominance.